Decreased Density of Perineuronal Net in Prelimbic Cortex Is Linked to Depressive-Like Behavior in Young-Aged Rats - Yu, Zhoulong; Chen, Na; Hu, Die; Chen, Wenxi; Yuan, Yi; Meng, Shiqiu; Zhang, Wen; Lu, Lin; Han, Ying; Shi, Jie (Frontiers in Molecular Neuroscience, 2020)
Perineuronal nets (PNNs) are condensed extracellular matrix structures regulating developmental plasticity and protecting neurons against oxidative stress. PNN abnormalities have been observed in various psychiatric disorders such as schizophrenia and bipolar disorder, but the relationship between PNN density and depression still remains unclear. In the present study, we examined the density and components of PNNs including aggrecan, neurocan and Tenascin-R in the prelimbic cortex (PrL) after chronic unpredictable mild stress (CUMS). We found that depressive-like behaviors were induced after 30 days of CUMS accompanied by decreases in PNN+ cell density and aggrecan expression in the PrL. In addition, rats subjected to 20 days of CUMS were separated into vulnerable and resilient subpopulations that differ along several behavioral domains. Consistently, the density of PNNs and the expression level of neurocan in vulnerable group were decreased compared to control and resilient groups. Finally, we examined individual differences based on locomotion in a novel context and classified rats as high responding (HR) and low responding (LR) phenotypes. The density of PNNs and the expression level of neurocan in LR group were lower than HR group. Moreover, the LR rats were more susceptible to depressive-like behaviors compared with HR rats. Altogether, these results suggest that the density of PNNs in the PrL is associated with depressive-like behaviors in young-aged rats, and it may serve as a potential endophenotype or therapeutic target for depression.